5-Aminolevulinic acid promotes arachidonic acid biosynthesis in the red microalga Porphyridium purpureum - Kailin Jiao; Jingyu Chang; Xianhai Zeng; I-Son Ng; Zongyuan Xiao; Yong Sun; Xing Tang; Lu Lin (Biotechnology for Biofuels, 2017)
Abstract Background The microalga Porphyridium purpureum within Rhodophyta abundantly produces several valuable proteins, polysaccharides, pigments and long-chain polyunsaturated fatty acid; it is especially effective in accumulating arachidonic acid (ARA). However, this high ARA yield is always achieved in conditions unfavourable for cell growth. In this study, we present a method for obtaining desirable ARA levels from P. purpureum while simultaneously promoting cell growth using appropriate concentrations of the growth hormone 5-Aminolevulinic acid (5-ALA). Results Both the biomass and the ARA content of P. purpureum were enhanced by stimulation with 20 mg/L 5-ALA, leading to an optimal ARA yield of 170.32 mg/L—a 70.82% increase compared with control conditions. This ARA yield is the highest ever reported for microalgae. Based on variations in the fatty acid composition, total lipids, total proteins, total carbohydrates and pigment content during the cultivation period, we propose that the accumulation of ARA stimulated by 5-ALA occurs at the expense of other UFAs and total proteins, which may be related to decreased zeaxanthin. Lipidomic analysis revealed that triacylglycerols (TAGs) accounted for 47.5 ± 3.6% of all detected lipids, followed by phosphatidylglycerol (PG) and digalactosyldiacylglycerol (DGDG). As the levels of the most abundant TAGs increased under 5-ALA promotion and because 78.1 ± 3.4% (by weight) of detected TAG-branched chains contained ARA, the increase of ARA was mainly caused by TAG accumulation. Conclusions This work demonstrated a simple and effective strategy to promote both biomass and ARA yield in P. purpureum by introducing a small amount of 5-ALA. These results are helpful for understanding the microalgae metabolic pathways affected by phytohormones and for guiding the development of bioproducts from microalgae.